1993
DOI: 10.1128/mcb.13.9.5469
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transfer and expression of reconstructed yeast artificial chromosomes containing normal and translocated BCL2 proto-oncogenes.

Abstract: The goal of this study was to determine whether it will be feasible to study the expression of a large, human gene, such as the BCL2 proto-oncogene, by DNA transfection. The BCL2 proto-oncogene is 230 kb in size and is deregulated in tumor cells by translocation into the immunoglobulin heavy-chain locus. Yeast artificial chromosomes (YACs) containing the human BCL2 gene were altered by homologous recombination in Saccharomyces cerevisiae to yield replicas of the normal and translocated alleles. Constructions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The human c-abl oncogene (ABL1), located at 9q34, where the consistent t(9;22)(q34;ql 1) translo cation in chronic myelocytic leukemia occurs, has its most 5' exon located 200 kb upstream of the remaining c-abl exons and shows a remarkable genomic structure, and transcription and splicing organization (Bernards et al, 1987). The Bcl2 proto oncogene (BCL2), identified at the breakpoint in lymphoma cells bearing the t( 14; 18) translocation, spans 230 kb of DNA (Silverman et al, 1993). The molecular analysis of YAC B45C11 has shown that FLI1 spans about 120 kb of DNA and will greatly expedite the structural study of this gene, disrupted by the ES and PNE chromosomal translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human c-abl oncogene (ABL1), located at 9q34, where the consistent t(9;22)(q34;ql 1) translo cation in chronic myelocytic leukemia occurs, has its most 5' exon located 200 kb upstream of the remaining c-abl exons and shows a remarkable genomic structure, and transcription and splicing organization (Bernards et al, 1987). The Bcl2 proto oncogene (BCL2), identified at the breakpoint in lymphoma cells bearing the t( 14; 18) translocation, spans 230 kb of DNA (Silverman et al, 1993). The molecular analysis of YAC B45C11 has shown that FLI1 spans about 120 kb of DNA and will greatly expedite the structural study of this gene, disrupted by the ES and PNE chromosomal translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FLI 1 is a very large gene: other genes, previously localized at the site of consistent chromosomal translocations, have been shown to span large segments of DNA and to have complex organizations (Bernards ct al., 1987;Silverman et al, 1993). The human c-abl oncogene (ABL1), located at 9q34, where the consistent t(9;22)(q34;ql 1) translo cation in chronic myelocytic leukemia occurs, has its most 5' exon located 200 kb upstream of the remaining c-abl exons and shows a remarkable genomic structure, and transcription and splicing organization (Bernards et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Protein bands were visualized after staining in a solution containing 0.25% Coomassie Brilliant Blue R-250, 45% methanol, and 10% acetic acid. For immunodetection, proteins separated by SDS-PAGE were electroblotted at 100 V for 1 h at 4°C onto reinforced nitrocellulose (NitroPure, Osmonics Inc., Westborough, MA) as described (23). The transfer buffer was 25 mM Tris-base, pH 8.0, and 190 mM glycine, pH 8.3.…”
Section: Figmentioning
confidence: 99%
“…Proteins separated by SDS-PAGE were electroblotted at 100 V for 1 h at 4°C, onto reinforced nitrocellulose (NitroPlus, Micron Separations, Inc., Westborough, MA) as described (32). The transfer buffer was 25 mM Tris base, pH 8.0, 190 mM glycine (pH 8.3).…”
Section: Construction Of Glutathione S-transferase (Gst) Fusionmentioning
confidence: 99%